2008
DOI: 10.1080/00016340801915127
|View full text |Cite
|
Sign up to set email alerts
|

Impaired maternal cognitive functioning after pregnancies complicated by severe pre‐eclampsia: a pilot case‐control study

Abstract: Maternal memory seems to be impaired after pregnancies complicated by severe pre-eclampsia. This effect cannot be attributed to depression and/or anxiety or method of anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 11 publications
4
89
1
4
Order By: Relevance
“…In the present study, no significant differences were observed between the pregnant women and the nonpregnant women on tasks of visuospatial abilities, although women tended to have lower scores on the Mental Rotations (a spatial task) compared with controls. While there is some inconsistency, most studies found no differences in performance between pregnant women and nonpregnant controls on spatial tasks (Brussé, Duvekot, Jongerling, Steegers, & De Koning, 2008;Eidelman et al, 1993;Glynn, 2010;Sharp et al, 1993).In contrast to previous studies, women in the pregnancy group performed more poorly on a processing speed task compared with the controls (de Groot, et al, 2003;de Groot, et al, 2006;Harris et al, 1996;Vanston & Watson, 2005). A factor that may account for the inconsistency is the use of different time intervals for completion of processing speed tasks.…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…In the present study, no significant differences were observed between the pregnant women and the nonpregnant women on tasks of visuospatial abilities, although women tended to have lower scores on the Mental Rotations (a spatial task) compared with controls. While there is some inconsistency, most studies found no differences in performance between pregnant women and nonpregnant controls on spatial tasks (Brussé, Duvekot, Jongerling, Steegers, & De Koning, 2008;Eidelman et al, 1993;Glynn, 2010;Sharp et al, 1993).In contrast to previous studies, women in the pregnancy group performed more poorly on a processing speed task compared with the controls (de Groot, et al, 2003;de Groot, et al, 2006;Harris et al, 1996;Vanston & Watson, 2005). A factor that may account for the inconsistency is the use of different time intervals for completion of processing speed tasks.…”
contrasting
confidence: 39%
“…In the present study, no significant differences were observed between the pregnant women and the nonpregnant women on tasks of visuospatial abilities, although women tended to have lower scores on the Mental Rotations (a spatial task) compared with controls. While there is some inconsistency, most studies found no differences in performance between pregnant women and nonpregnant controls on spatial tasks (Brussé, Duvekot, Jongerling, Steegers, & De Koning, 2008;Eidelman et al, 1993;Glynn, 2010;Sharp et al, 1993).…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…Women with a history of early onset PE report similar levels of psychosocial distress on average 14 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] years after pregnancy as measured by anxiety, (absence of) social support, and personality constructs optimism and Type D personality, when compared to a group without PE. A significantly higher level of depressive symptoms and fatigue was observed, albeit with a very small effect size.…”
Section: Discussionmentioning
confidence: 97%
“…In a systematic review on this topic, Delahaije and colleagues described six studies on anxiety, depression, and PTSD in women following PE. Two studies were prospective [13,16], and four utilized a historic cohort [15,[17][18][19]. Depressive symptoms, PTSD, or anxiety were assessed a few months up to on average seven years after pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…74 This is unrelated to scores of depression, anxiety or attention. 74 It is possible that women who have had severe pre-eclampsia or eclampsia have permanent white matter damage, or their memory is impaired by the emotional trauma of a severe illness.…”
Section: Pre-eclampsia and Future Mental Healthmentioning
confidence: 99%